2005
DOI: 10.1002/jobm.200410355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of certain bioactive plant extracts on clinical isolates of β‐lactamase producing methicillin resistant Staphylococcus aureus

Abstract: Ethanolic extracts and some fractions from 10 Indian medicinal plants, known for antibacterial activity, were investigated for their ability to inhibit clinical isolates of beta-lactamase producing methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-sensitive S. aureus (MSSA). Synergistic interaction of plant extracts with certain antibiotics was also evaluated. The MRSA test strains were found to be multi-drug resistant and also exhibited high level of resistance to common beta-lactam antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 21 publications
1
104
0
2
Order By: Relevance
“…In order to assess the effect of combinations of ethanolic extract and antibiotic, the MIC values for antibiotic were determined to be as a reference point for defining the interactions [26] . Synergistic effects resulting from the combination of antibiotics with various plant extracts have been studied earlier against MRSA or MSSA [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] . From this study, ethanolic extract of E. elaterium fruits is very efficient in treating infectious diseases caused by MRSA and may also helpful for treating diseases caused by C. albicans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the effect of combinations of ethanolic extract and antibiotic, the MIC values for antibiotic were determined to be as a reference point for defining the interactions [26] . Synergistic effects resulting from the combination of antibiotics with various plant extracts have been studied earlier against MRSA or MSSA [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] . From this study, ethanolic extract of E. elaterium fruits is very efficient in treating infectious diseases caused by MRSA and may also helpful for treating diseases caused by C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to light was avoided to prevent the loss of effective ingredients. Approximately [30][31][32][33][34][35][36][37][38][39][40] g of dried material were mixed thoroughly with magnetic stirrer in 200 mL of 80% ethanol at room temperature and the mixture left for 24 h. The insoluble materials were removed by centrifugation at 10 000 rpm for 10 min at 4 曟. Then, the extract was evaporated to dryness at 37 曟.…”
Section: Plant Extractionmentioning
confidence: 99%
“…Research on synergism is very limited and few studies have been reported (Nascimento et al 2000, Aburjai et al 2001, Aqil et al 2005. Thus, in our research, we evaluated in vitro synergism between extracts of M. glomerata, P.…”
mentioning
confidence: 94%
“…23 Other bioactive plant extracts, containing flavonoids and phenols as major components, have proven effective against MRSA and a range of Gram-negative bacteria. 27,28 From the oral perspective, naringin, a flavonoid extract from grapefruit, has shown promise in the growth inhibition of A. actinomycetemcomitans and P. gingivalis in planktonic phase. 29 Polyphenols extracted from hop extracts and cranberry have shown activity against streptococcal species associated with dental caries [30][31][32] and a citrus extract combined with lemon juice and lemon grass has been used successfully to treat oral candidosis.…”
Section: Discussionmentioning
confidence: 99%